2018
DOI: 10.1177/2045125317753340
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of the pharmacological management of benzodiazepine withdrawal, dependence, and discontinuation

Abstract: Background:Benzodiazepines (BZDs) are among the most prescribed sedative hypnotics and among the most misused and abused medications by patients, in parallel with opioids. It is estimated that more than 100 million Benzodiazepine (BZD) prescriptions were written in the United States in 2009. While medically useful, BZDs are potentially dangerous. The co-occurring abuse of opioids and BZD, as well as increases in BZD abuse, tolerance, dependence, and short- and long-term side effects, have prompted a worldwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 93 publications
2
60
0
4
Order By: Relevance
“…Even if all of these cases resulted from kava use, the estimated risk would be less than 0.3 cases per one million daily doses [ 167 , 173 ], which is still superior to some, if not all, commonly used anxiolytic agents. At the same time, stress and anxiety are becoming more prevalent among the general population [ 174 ], while current pharmacologic treatments have only a modest clinical effect and carry a high burden of side effects [ 175 , 176 ]. Thus, there is an unmet clinical need for novel anxiolytics to achieve better anxiety management with minimal adverse effects [ 177 ].…”
Section: Safety Of Kava and Its Hepatotoxic Riskmentioning
confidence: 99%
“…Even if all of these cases resulted from kava use, the estimated risk would be less than 0.3 cases per one million daily doses [ 167 , 173 ], which is still superior to some, if not all, commonly used anxiolytic agents. At the same time, stress and anxiety are becoming more prevalent among the general population [ 174 ], while current pharmacologic treatments have only a modest clinical effect and carry a high burden of side effects [ 175 , 176 ]. Thus, there is an unmet clinical need for novel anxiolytics to achieve better anxiety management with minimal adverse effects [ 177 ].…”
Section: Safety Of Kava and Its Hepatotoxic Riskmentioning
confidence: 99%
“…(BZDs) are commonly used psychotropic drugs for treating conditions such as insomnia and anxiety in primary care, although their long-term use is associated with considerable adverse effects [1][2][3]. Despite guidance advocating use of non-pharmacological, psychological treatments first-line (1), and restricting BZDs to only short-term use if needed (2), numerous studies have shown that BZDs are still overprescribed and commonly used long-term [4][5][6].…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…[ 21 ] In the case of long-acting agents such as diazepam, withdrawal symptoms manifest only about 5–7 days after abrupt discontinuation, while they are more quickly evident in case of drugs like lorazepam. [ 22 ]…”
Section: Antipsychoticsmentioning
confidence: 99%